Targeted prevention of radiation-induced oral mucositis by glutathione-modified liposome coated K12 probiotics and clinical study - ZhiHui Li; Dan He; Ye Zhang; Zhou Shi; Quanjin Tang; Zixia Li; Xingchen Peng; Dong Li; Daijun Zhou (Materials Today Bio)
Radiation-induced oral mucositis (RIOM) is the most common oral complication faced by patients with head and neck cancer undergoing radiotherapy or chemotherapy, significantly diminishing their quality of life. While previous studies have investigated single K12 probiotics for RIOM, they often lacked stability, free radical scavenging activity, and precise oral targeting. To overcome these challenges, we developed K12@Lip@GSH, an innovative oral probiotic that encapsulates K12 within liposomes to enhance stability and scavenging efficacy, while utilizing a glutathione (GSH) transporter-mediated targeting mechanism that exploits the favorable the overexpression of GSH transporters in RIOM. Evaluations conducted in RIOM mouse models subjects demonstrated favorable outcomes, including a reduction in ulcer size, increased epithelial cellularity and mucosal thickness, enhanced epithelial proliferation, and decreased apoptosis. Genomic analysis further indicated improvements in mRNA pathways associated with the recovery from RIOM. Additionally, K12@Lip@GSH was shown to restore the balance of oral microbiota and reduce the abundance of oral anaerobes in RIOM mice. Subsequently, the safety and efficacy of K12@Lip@GSH were confirmed through further single-arm, single-center prospective clinical trials. The clinical trial data demonstrated a manageable safety profile in the cohort of 22 enrolled patients. Treatment-related adverse events (TRAEs) were infrequent, occurring in only 4.5 % of participants, with reported symptoms including flatulence and dyspepsia. Although 59.1 % of patients experienced oral mucositis (OM), the incidence of severe OM (grade 4) was 0.0 %, and no interruptions in radiotherapy treatment occurred due to OM. Overall, K12@Lip@GSH shows promise as an adjuvant strategy for improving radiation-induced oral mucositis (RIOM) in cancer patients undergoing radiotherapy.